Analisis Ketersediaan dan Kualitas Sanitasi di Kawasan Ekonomi Khusus Mandalika - Lalu Muhammad Aby Dujana; Hilman Ahyadi; Ernawati Ernawati; Isrowati Isrowati; M. Restu Rabani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Lombok Island, particularly the Kawasan Ekonomi Khusus (KEK) Mandalika, has rapidly developed as a global tourist destination, attracting a significant annual increase in visitor numbers. This growth necessitates the provision of adequate facilities, especially sanitation facilities, which play a crucial role in enhancing visitor comfort and experience as well as supporting sustainable tourism principles. This study aims to identify the availability of sanitation facilities and analyze sanitation quality at KEK Mandalika through a quantitative approach. Data collection was conducted using checklists to evaluate facility conditions and laboratory tests to measure water quality parameters such as pH, total dissolved solids (TDS), and salinity. The results indicate that several sanitation facilities have not met comfort standards and require improvement. Water quality based on tested parameters showed pH within normal ranges, TDS exceeding quality standards, and salinity tests indicating brackish water with low salinity. This research highlights an urgent need to enhance facilities, particularly those that are disability-friendly, to support inclusive comfort and accessibility, as well as to improve clean water quality. With such facility improvements, KEK Mandalika is expected to maintain its reputation as an environmentally friendly, safe, and high-quality tourist destination. The findings also offer recommendations for infrastructure enhancement and easier access, which ultimately can minimize the environmental impact of tourism activities.